Insulin-like signaling pathway functions in integrative response to an olfactory and a gustatory stimuli in Caenorhabditis elegans - Jiu, Ya-Ming (Protein Cell, 2010)
Animals integrate various environmental stimuli within the nervous system to generate proper behavioral responses. However, the underlying neural circuits and molecular mechanisms are largely unknown. The insulinlike signaling pathway is known to regulate dauer formation, fat metabolism, and longevity in Caenorhabditis elegans (C. Elegans). Here, we show that this highly conserved signaling pathway also functions in the integrative response to an olfactory diacetyl and a gustatory Cu(2+) stimuli. Worms of wild-type N2 Bristol displayed a strong avoidance to the Cu(2+) barrier in the migration pathway to the attractive diacetyl. Mutants of daf-2 (insulin receptor), daf-18 (PTEN lipid phosphatase), pdk-1 (phosphoinositide-dependent kinase), akt-1/-2 (Akt/PKB kinase) and sgk-1 (serum- and glucocorticoidinducible kinase) show severe defects in the elusion from the Cu(2+). Mutations in DAF-16, a forkhead-type transcriptional factor, suppress the integrative defects of daf-2 and akt-1/-2 mutants. We further report that neither cGMP nor TGFβ pathways, two other dauer formation regulators, likely plays a role in the integrative learning. These results suggest that the insulin-like signaling pathway constitutes an essential component for sensory integration and decision-making behavior plasticity.